2021
DOI: 10.1186/s42779-021-00093-5
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and microbial profiling establish “Eu” (a traditional fermented beverage of Toto people) as a probiotic health drink

Abstract: Abstract“Eu,” is a traditional millet-based mild alcoholic beverage consumed by the Toto tribe of West Bengal. Eu is prepared through the fermentation of millet with locally groomed starter culture “Moaa.” The study highlighted the overview of the traditional process of Eu preparation along with its molecular and biochemical characterization. Semi-structured interviews were conducted for collecting the ethnobotanical data and the samples. We have also included qualitative assays like acute toxicity, antioxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…The network pharmacology study revealed several Eu compounds interacted with the MAPK1, modulating its expression. Furthermore, a previous report on the in vitro antioxidant assay of Eu proved that Eu can reduce oxidative stress (Bhattacharjee et al 2021). Thus, the antioxidant property of Eu can reduce the expression of MAPK, plummeting the chances of GI oncogenic onset.…”
Section: Effect Of the Compounds Of Eu In On The Prevention Of Gastro...mentioning
confidence: 93%
See 2 more Smart Citations
“…The network pharmacology study revealed several Eu compounds interacted with the MAPK1, modulating its expression. Furthermore, a previous report on the in vitro antioxidant assay of Eu proved that Eu can reduce oxidative stress (Bhattacharjee et al 2021). Thus, the antioxidant property of Eu can reduce the expression of MAPK, plummeting the chances of GI oncogenic onset.…”
Section: Effect Of the Compounds Of Eu In On The Prevention Of Gastro...mentioning
confidence: 93%
“…The collected liquid sample (Eu) was subjected to analysis of the biochemical composition and the nutritional value using the standard protocol. Previously, we have done a lyophilised methanolic extraction of Eu for GC-MS analysis to obtain the bioactive compounds in the brew (Bhattacharjee et al 2021).…”
Section: Nutritional Composition Of Eumentioning
confidence: 99%
See 1 more Smart Citation